“A question of self-interest”: A brief history of 50 years of international student policy in Canada - McCartney, Dale M. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2021)
This article offers a periodization of the history of international student policy in Canada since 1970. It draws on archival sources at seven public post-secondary institutions in British Columbia and Ontario, as well as governmental discussion in both provinces and at the Federal level, and scholarly writing about international students within the Canadian Journal of Higher Education to construct this history. Four key periods are identified: the emergence of differential fee policies in the 1970s; an era of institutional recruitment efforts in the 1980s and 1990s; a period of active government recruitment in the 2000s; and an era of bifurcating priorities as governments expanded their recruitment efforts but scholars began to question the international student project in Canada. The article shows changes in international student policy over the past half-century, but also reveals continuities, most notably a sustained emphasis on serving Canada’s perceived national interests.